LEADER’S PERSONAL ENTREPRENEURIAL CHARACTERISTICS IN FAMILY OWNED SMALL ENTERPRISES IN VAVUNIYA DISTRICT, SRI LANKA - Pushpanathan, A. (Macmillan Publishers India, 2008)
The leadership in the family business is aimed at helping business-owning families understand and implement the extra dimensions of leadership that family firm require. The entrepreneur believes that the organization cannot remain competitive without effectiveleadership style. The leader of the firm has some personal entrepreneurial characteristics for achieving success in his/her business. The Management Systems International (MSI)/ McBer team identified ten key Personal Entrepreneurial Characteristics (PECs) that separate successful entrepreneurs from unsuccessful ones. The main objective of this study is to analyze the leader’s personal entrepreneurial characteristics (PECs) in family owned small enterprises in Vavuniya District, Sri Lanka. The purpose of this article is to provide an explanation for the leader’s personal entrepreneurial characteristics in family owned small enterprises. Three factors –Achievement competencies, Planning competencies, and power competencies – were analyzed from 375 small entrepreneurs in Vavuniya District, Sri Lanaka. And also mean value of individual variables were ranked in order of their importance. Principle components factor analysis is used for analyzing the data with Varimax rotation in SPSS package
Keywords: Leadership Styles; Family Owned Small Enterprise; Family Owned Small Enterprise